Angústia e história um reencontro da liberdade em Kierkegaard - Santos, Maria Deiviane Agostinho dos (2014)
Kierkegaard discusses the fundamental metaphysical categories through human existence. It is not, in this work, only to establish ontological relations, but to discover, if possible, how Kierkegaard puts the interiority to the externality in an earlier conception of the History itself. This effort is the key issue facing the condition of the individual in history, since their absence to their historical and current can overcome. Focused on the implication of the concept of anxiety, of freedom and the history itself. This work aims to establish the foundations of freedom for its reunion, giving through the dialectical conception and, at the same time, the possibility of rupture that the man is able to establish in the history, an answer to the questions that pertain to freedom and anxiety. This work touches finally the question of the ethics of love, as the reconciliation of the man with himself.